El Excentrico, 1967-06-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 20, 1967 [20 de junio de 1967]. No volume or issue number. Cover has a headshot of Yvonne Cook, who had graduated from the Metropolitan Adult Education Program. The headline reads, "Mrs. Yvonne Cook, 1967 Graduate Metropolitan Adult Education Program."